Entwicklung der öffentlichen Gesundheitsausgaben - Götz Zeddies (Wirtschaftsdienst, 2023)
– In light of demographic change, health expenditures of the German state should rise considerably in future. On the basis ofthe 15th population forecast of the German Federal Statistical Office, health expenditures of the German public health care system areprojected until the year 2050. As the calculations show, public health care expenditures of the German federal state will almost triple bythen.. In Germany, public health care expenditures are financed by social security contributions raised on gross wages. These wages,according to long-term economic projections of the OECD, will also rise considerably by the year of 2050. However, since public healthcare expenditures will increase more than gross wages due to demographic change, contribution rates or tax subsidies to the Germanstatutory health insurance will have to be increased.
Keywords: H11; H41; H51; 330